Peningkatan Hasil Belajar Siswa Melalui Model Inkuiri pada Pembelajaran Ilmu Pengetahuan Alam dan Sosial di Kelas IV di MIS An-Nizham Kota Jambi - Yusromadona Yusromadona; Rhesti Laila Ulfa (SOSIAL : Jurnal Ilmiah Pendidikan IPS, 2025)
This study aims to improve student learning outcomes through the application of inquiry learning models in Natural and Social Sciences (IPAS) subjects in class IV MIS An-Nizham Jambi City. The background of this study is based on the low involvement and understanding of students in the IPAS material, as well as the dominance of the lecture method used by teachers in the learning process. This study is a classroom action research (PTK), data was collected through (1) Teacher observation sheets, (2) Student observation sheets, (3) Student learning outcome test questions. Data analysis in this study used the percentage formula. Data analysis in this study used the percentage formula. The increase in student learning outcomes in IPAS learning in cycle I has not reached the Minimum Completion Criteria value that has been set at MIS An-Nizham Jambi City with a percentage value of 74.4% (good category), while when applying the inquiry learning model to Natural and Social Sciences learning in cycle II showed that 25 students with a percentage value of 91.15% were in the very good category and had reached the KKM but 2 more students had not reached the KKM. Based on the results of data analysis, it can be concluded that by implementing the inquiry learning model, it can increase teacher and student activities, and can improve student learning outcomes, in Natural and Social Sciences lessons in class IV MIS An-Nizham, Jambi City